Enhancing dye rejection and antifouling resistance of thin film nanocomposite nanofiltration membranes by the incorporation of glutamic acid functionalized graphene oxide - Maziya, Khona; Kotze, Izak; Richards, Heidi Lynn (Frontiers in Membrane Science and Technology, 2025)
To enhance membrane performance of nanofiltration (NF) membranes for dye wastewater treatment, thin film nanocomposite (TFN) membranes embedded with glutamic acid brush modified graphene oxide (GO-GLU) were fabricated. In this current study, GO-GLU was introduced to the selective polyamide (PA) layer which was prepared via interfacial polymerization of organic trimesoyl chloride (TMC) and aqueous m-phenylenediamine (MPD) on a polysulfone (PSF) support. Water permeability and dye rejection with methyl orange (MO) and methylene blue (MB) were used to evaluate membranes performance. The evaluation of TFN membranes via WCA, FTIR, SEM, and AFM demonstrated that GO-GLU nanosheets enhanced hydrophilicity. The fabricated GO-GLU TFN membrane attained a water permeance of 14.11 L/m2h at the optimal GO-GLU dosage of 0.10 wt%, with 99.18% MB rejection and 67.18% MO rejection. Furthermore, it displayed superior antifouling characteristics against Bovine Serum Albumin (BSA) than the virgin TFC membrane and potentially good operation stability performance after 3 cycles. The results proved that addition of GO-GLU nanosheets enhanced membrane performance. The TFN membranes provide excellent performance in effectively removing of dyes from both synthetic and river water samples, rendering them a suitable alternative for wastewater treatment. The study sheds fresh light on the construction of NF membranes by using GO-GLU nanosheets to boost the membranes hydrophilicity and antifouling properties.